Comparison of current Spray models under high pressure and high temperature engine relevant conditions - Vogel, Thomas; Rieß, Sebastian; Lutz, Michael; Wensing, Michael; Leipertz, Alfred (24th European Conference on Liquid Atomization and Spray Systems (ILASS-Europe), 2011)
The liquid spray length is a key parameter in the optimization of diesel combustion processes. Since 1960 several spray models have been developed in order to describe the spray propagation with and without the influ-ence of the temperature of the ambient gas atmosphere. However, since the time most propagation models were developed injection systems and the thermodynamic conditions under which the fuels are injected have changed much. The present investigation compares more than ten spray models to measurements performed in a high temperature and high pressure cell in order to simulate the conditions in modern diesel engines using two different modern injectors. In addition to the penetration-model-comparison the nozzle exit velocity is determined via the differentiation of an origin-shifted root of time curve fitted to measured data. The results are compared to the corresponding Bernoulli-velocity in order to calculate the discharge coefficient. The discharge coefficient is compared to the pressure drop of the nozzle and the discharge Reynolds number. In order to simulate different engine operation different ambient conditions were defined into which the spray was injected. The effect of each single parameter on the spray formation can be identified since the parameters are controlled separately. These parameters varied are the ambient gas temperature (523 K, 623 K, 723 K, 823 K and 923 K), the ambient gas pressure (1 MPa, 3 MPa, 5 MPa, 7 MPa and 9 MPa) and the fuel pressure (40 MPa, 80 MPa, 120 MPa, 160 MPa and 200 MPa) while fuel temperature (363 K) and injection duration (450 μs) were kept constant. The injection chamber was permanently scavenged with nitrogen thus ignition and combustion were suppressed, even at high temperatures. Two injectors from two different vendors were used. The first injector is a piezo-actuated servo-hydraulic 8-hole injector (Bosch) with orifice diameter of 152 μm while the length of the nozzle is 1 mm. The second injector is a 7-hole and also piezo-actuated and servo-hydraulic injector (Continental). The orifice diameter of this injector is 120 μm and the length of the nozzle is 720 μm. In order to measure the spray parameters like penetration and spray cone angle a Mie-scattering setup consisting of four flash lamps and one sensitive CCD-camera was installed. At every operating condition a total of 16 points of time after SOI and 32 images for each point of time were recorded. Firstly, spray models from literature were compared to identify main parameters influencing the penetration depth vs. time. A dimension analysis is given in Table 1. The main parameters are fuel pressure difference, orifice diameter and gas density. The exponent of time given varies from 0.48 to 0.64. Some models include also the orifice length and the gas temperature. All operating points were compared to all spray models. Under the present conditions the models of Taylor and Walsham, Dent, Lustgarten, Hiroyasu and Arai, Desantes, Arregle and Sazhin were much closer to the measurements data than the rest of the models, especially at low temperature conditions. At high temperature and pressure conditions all models differ much from the measurements. The measured penetration depth reaches a stationary state, where injection rate and evaporation rate reach the same value so that the penetration length stays nearly constant. None of the models includes the effect of evaporation completely. All models predicted a continuously increasing penetration depth. Overall, no model predicted the spray accurate at all operating condi-tions although some models are close to the measured data at some operating points. The determination of the nozzle exit velocity allowed the calculation of typical, operating point dependent, discharge coefficients. Especially under high injection pressure conditions the analysis carried out a significant difference in the throttling behavior which is not only caused by the orifice diameter and length but also by the injection system itself.<br